PEDAGOGICAL PRINCIPLES OF THE HISTORY OF MUSIC PEDAGOGY AND DIDACTIC POSSIBILITIES OF ITS USE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article reveals the pedagogical foundations of the history of music pedagogy and the didactic possibilities of its use, which, according to the authors, are the most significant and relevant. Among them is the mono-artistic approach, which allows studying individual types of art in the system of general education, primary vocational secondary and higher vocational education.